Interdependence of Hedge Accounting Effects and profitability of Banks during the Covid-19 Pandemic - Evidence from Banks in Croatia - Hrvoje PERČEVIĆ; Marina ERCEGOVIĆ (Communications of International Proceedings, 2022)
As many of the bank's customers faced financial difficulties during the COVID-19 pandemic, the banks were significantly exposed to the rising credit risk and probability of default by their customers. To prevent excessive recognition of impairment losses in banks and maintain the stability of the financial system during the pandemic crisis, banks were advised and appealed to the recognition of impairment losses on long-term stable outlook and considering relief measures, not on current extraordinary circumstances. Despite all, many banks have experienced a decrease in their profitability rates. Many banks around the world have implemented hedge accounting to properly present the effects of their hedging activities on financial position and performance. The main purpose of this paper is to investigate whether banks in Croatia that applied hedge accounting achieved higher profitability rates than those that did not apply hedge accounting during the COVID-19 pandemic, as well as to determine whether there is a significant interdependence between the effects of hedge accounting recognized in the financial statements of banks in Croatia and profitability rates. The research covers all banks in Croatia that operated in the period from 2019 to 2021. Data were collected from the annual reports of banks in Croatia. Descriptive statistics methods were used to investigate the trend of bank profitability ratios in Croatia during the observed period. Correlation analysis and multiple linear regression were used to identify the interdependence between the effects of hedge accounting (recognized in bank financial statements) and the profitability rates of banks in Croatia that applied hedge accounting during the research period. The research results showed that banks in Croatia that applied hedge accounting during the Covid-19 pandemic achieved higher profitability rates on average than those that did not apply hedge accounting, but there was not enough evidence to support the claim that there is a statistically significant interdependence between the effects of hedge accounting and profitability rates of banks in Croatia. In other words, the results of the research do not indicate that the effects of hedge accounting significantly contributed to the profitability of banks in Croatia.
Keywords: Hedge accounting; return on assets (ROA); COVID-19 pandemic; banks; Croatia